Migraine and cognition in children: a controlled study - Andréa Regina Correa Moutran; Thaís Rodrigues Villa; Luciana Aparecida Sobirai Diaz; Maria Helena da Silva Noffs; Mariana Machado Pereira Pinto; Alberto Alain Gabbai; Deusvenir de Souza Carvalho (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Evaluate the cognitive functions of children with migraine and compare them to A control group. METHOD: 30 migraineur children and 30 control group children without migraine, age ranging from 8 to 12 years old, were subjected to a cognitive functions assessment with Wechsler Intelligence Scale for Children (WISCIII). RESULTS: Although both groups had a normal cognitive performance, children with migraine had significantly worse scores compared to the control group in the subtests of Information, Arithmetic, Vocabulary, Object Assembly and in the Indexes of Perceptual Organization, Resistance to Distraction and Processing Speed. CONCLUSION: Children with migraine had impairment in some cognitive functions such as attention, memory, information speed, and perceptual organization compared to the control group.